Religiosity, Secular Participation, and Cultural Socialization: A Case Study of the 1933–1942 Urban English Cohort - McAndrew, Siobhan (Journal for the scientific study of religion, 2020)
The nature of secularization is of enduring interest in the social science of religion. Numerous recent papers have established downward cohort trends as characterizing religious change. We examine potential mechanisms by assessing cultural participation and secular engagement during the formative period of one cohort. We provide estimates of active and nominal religiosity, nonreligion and religious belief for those born between 1933 and 1942, using multiple surveys fielded between 1957 and 2018. We model the association between religiosity and secular cultural and social participation for this cohort in 1957, then examine how cultural socialization in childhood relates to religiosity in their later adulthood using surveys fielded between 2005 and 2007. Increased secular competition is found to be associated with less active religiosity. These trends were underpinned by an ethic of increasing autonomy for the young. We conclude by affirming the link between increasing secular competition, long-run modernization, and changing cultural socialization.